Examining the Impact of Climate Change on Agriculture Products in the Province of Jawzjan (Case Study: Certain Villages in Sheberghan City) - MAKHDOM, Mohammad Ayoob; ZOHOR, Ahmad Kanishka; INTEZAR, Aburaihan (Journal for Research in Applied Sciences and Biotechnology, 2024)
A region's weather and climate patterns are impacted by climate change over an extended period of time. Rising temperatures, altered precipitation patterns, rising sea levels and other modifications to meteorological conditions are some of these changes. Numerous facets of existence, including the environment, economy, and human communities, may be significantly impacted by climate change. Significant repercussions of climate change are possible, particularly in the agricultural sector. The production of food crops may be impacted by these changes because agricultural goods are dependent on local climate and weather. Pests and plant diseases may also become more prevalent due to climate change. Accordingly, higher temperatures and changed precipitation patterns can foster the growth of pests and illnesses, which will lower agricultural yields. Investigating how climate change affects agricultural products in Sheberghan City, Jawzjan Province, is the goal of this study. A questionnaire was used in fieldwork to perform this study. Six communities inside Sheberghan City—Toka, Qowchin, Jalalabad, Seshanba, Nokar Abad, and Afghan Tapa—were given 100 questionnaires in all. Four different types of questionnaires were produced and designed for the survey portion of this study. Of the 100 responders, 26 worked as farmers, 37 as gardeners, 8 as teachers, and 29 as traders in agricultural products. Using the SPSS26 program, the research was analyzed. The results showed that agricultural goods are significantly impacted by climate change, highlighting the significance of agriculture and agricultural products in the economy. The research findings indicate that the utilization of contemporary technology, such as smart irrigation systems and smart systems, can be one of the elements in growing agricultural products, and that the development of climate-adaptive agricultural methods can boost agricultural products. Farmers' interest can also be raised by government encouragement and assistance. The general conclusion that can be drawn from looking at the aforementioned elements is that agricultural products have been impacted by climate change and the creation of farmers' techniques for adapting to it.